The black bird oracle : a novel [large type] - Harkness, Deborah, 1965- (Harkness, Deborah, 1965- All souls series, 2024)
"Diana Bishop journeys to the darkest places within herself--and her family history--in the highly anticipated fifth novel of the beloved #1 New York Times bestselling All Souls series. Deborah Harkness first introduced the world to Diana Bishop, Oxford scholar and witch, and vampire geneticist Matthew de Clairmont in A Discovery of Witches. Drawn to each other despite long-standing taboos, these two other-worldly beings found themselves at the center of a battle for a lost, enchanted manuscript known as Ashmole 782. Since then, they have fallen in love, traveled to Elizabethan England, dissolved the Covenant between the three species, and awoken the dark powers within Diana's family line. Now, Diana and Matthew receive a formal demand from the Congregation: They must test the magic of their seven-year-old twins, Pip and Rebecca. Concerned with their safety and desperate to avoid the same fate that led her parents to spellbind her, Diana decides to forge a different path for her family's future and answers a message from a great-aunt she never knew existed, Gwyneth Proctor, whose invitation simply reads: It's time you came home, Diana. On the hallowed ground of Ravenswood, the Proctor family home, and under the tutelage of Gwyneth, a talented witch grounded in higher magic, a new era begins for Diana: a confrontation with her family's dark past, and a reckoning for her own desire for even greater power-if she can let go, finally, of her fear of wielding it"--